Structural and electrical properties of Bi6Ti5TeO22 thin films grown on Pt/Ti/SiO2/Si substrate - Choi, Chang-Hak; Choi, Joo-Young; Cho, Kyung-Hoon; Yoo, Myong-Jae; Choi, Jae-Hong; Nahm, Sahn; Kang, Chong-Yun; Yoon, Seok-Jin; Lee, Hwack-Joo (ELECTROCHEMICAL SOC INC, 2008)
Bi6Ti5TeO22 (BTT) thin films were well formed on a Pt/Ti/SiO2/Si substrate using radio frequency magnetron sputtering. The dielectric constant (k) of the BTT films grown at room temperature was relatively high, approximately 54, and increased with increasing growth temperature to reach a maximum value of 107 for the film grown at 500 degrees C. In particular, the 120 nm thick BTT films grown at 200-300 degrees C showed high k-values of 63-69 with a low dissipation factor (<= 1.3%) due to the presence of the small BTT crystals (similar to 5 nm). The leakage current density of this film was very low, approximately 2 x 10(-10) A/cm(2), at 3 V. Therefore, the BTT film grown at low temperatures (<= 300 degrees C) is a promising candidate material for metal-insulator-metal capacitors which require low processing temperatures. (C) 2008 The Electrochemical Society.
Keywords: DIELECTRIC CHARACTERIZATION; BI2O3-TIO2-TEO2 SYSTEM; OXYGEN ATMOSPHERE; PHASE-FORMATION; TRANSISTORS; CAPACITORS; ELECTRONICS